Systematic review and meta‐analysis of factors associated with post‐operative pancreatic fistula following pancreatoduodenectomy. Issue 5 (2nd November 2020) - Kamarajah, Sivesh K.; Bundred, James R.; Lin, Aaron; Halle‐Smith, James; Pande, Rupaly; Sutcliffe, Robert; Harrison, Ewen M.; Roberts, Keith J.; ,
Abstract: Background: Many studies have explored factors relating to post‐operative pancreatic fistula (POPF); however, the original definition (All‐POPF) was revised to include only 'clinically relevant' (CR) POPF. This study identified variables associated with the two International Study Group on Pancreatic Surgery definitions to identify which variables are more strongly associated with CR‐POPF. Methods: A systematic review identified all studies reporting risk factors for POPF (using both International Study Group on Pancreatic Fistula definitions) following pancreatoduodenectomy. The primary outcome was factors associated with CR‐POPF. Meta‐analyses (random effects models) of pre‐, intra‐ and post‐operative factors associated with POPF in more than two studies were included. Results: Among 52 774 patients All‐POPF ( n = 69 studies) and CR‐POPF ( n = 53 studies) affected 27% (95% confidence interval (CI95% ) 23–30) and 19% (CI95% 17–22), respectively. Of the 176 factors, 24 and 17 were associated with All‐ and CR‐POPF, respectively. Absence of pre‐operative pancreatitis, presence of renal disease, no pre‐operative neoadjuvant therapy, use of post‐operative somatostatin analogues, absence of associated venous or arterial resection were associated with CR‐POPF but not All‐POPF. Conclusion: In conclusion this study demonstrates wide variation in reported rates of POPF and that several risk factors associated with CR‐POPF are not used within risk prediction models. Data from this study can be used to shape future studies, research and audit across ethnic and geographic boundaries in POPF following pancreatoduodenectomy. Abstract : This study demonstrates wide variation in reported rates of post‐operative pancreatic fistula (POPF) and that several risk factors associated with clinically relevant POPF are not used within risk prediction models. Data from this study can be used to shape future studies, research and audit across ethnic and geographic boundaries in POPF following pancreatoduodenectomy.